2003
DOI: 10.1007/978-3-540-45175-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Users and Uses of Online Digital Libraries in France

Abstract: Abstract. This article presents a study of online digital library (DL) uses, based on three data sources (online questionnaire, Internet traffic data and interviews). We show that DL users differ from average Internet users as well as from classical library users, and that their practices involve particular contexts, among which personal researches and bibliophilism. These results lead us to reconsider the status of online documents, as well as the relationship between commercial and non-commercial Web sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Steinerova [16] describes DL usage patterns of Slovakian DL users as reported through questionnaires. Assadi et al [17] describe DL usage patterns in France through surveys, interviews and instrumented DLs. Saracevic [18] offers a broad conceptual framework for DL evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Steinerova [16] describes DL usage patterns of Slovakian DL users as reported through questionnaires. Assadi et al [17] describe DL usage patterns in France through surveys, interviews and instrumented DLs. Saracevic [18] offers a broad conceptual framework for DL evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…This platform was used to carry out a large number of usage studies in the context of the SensNet project. The precision of the content descriptions as well as the scalability of the CatService module allowed us to perform fine-grained focuses on particular kinds of sites or services: use of Web search engines [1], use of Digital Libraries [3]. Beside these specific studies, we combined content descriptions with topological and temporal indicators in a global approach of navigation, and showed off the strong link between page content, browsing dynamics and users' personal territories on the Web [4].…”
Section: Resultsmentioning
confidence: 99%
“…Koch et al (2004) found that a thorough log analysis can provide deeper understanding of the services and they may offer useful hypotheses for advanced user studies. Only Assadi et al (2003) presents an approach which relies on a combination of three methods: user-centric data analysis, online questionnaires and interviews.…”
Section: Combining Different Streams Of Log Datamentioning
confidence: 99%
“…A general study of the uses of a diversified population of remote users of a digital library is presented in Assadi et al (2003). Here the population was made up of university researchers and postgraduate students, as well as high school teachers and students or individuals performing personal research.…”
Section: Online Public Access Cataloguesmentioning
confidence: 99%
See 1 more Smart Citation